The Punitive Society - Foucault, Michel. author. aut Link
XIX, 320 p.
Keywords: These thirteen lectures on the 'punitive society,' delivered at the Collège de France in the first three months of 1973, examine the way in which the relations between justice and truth that govern modern penal law were forged, and question what links them to the emergence of a new punitive regime that still dominates contemporary society.